Escaping From Oppression In Steven Spielberg's The Color Purple Movie (1985): A Feminist Approach - Pradipta, Gunawan Sigit (2012)
The object of the research is a movie entitled The Color Purple directed by Steven Spielberg. The study focuses on the feminist perspective of the movie. The major problem of this study is to depict how Cellie escaping the oppression reflected in Steven Spielberg's The Color Purple movie. The objectives of the study are to analyze the structural elements of the movie and to analyze the movie based on the feminist perspective. This research is the qualitative approach. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie itself. The method of the data collection is documentation research. The technique of data analyzes is descriptive analyzes. The results of the research show the following conclusions. Firstly, based on the structural analysis, Steven Spielberg wants to deliver a message to the viewers that escape from oppression in The Color Purple occurred because of social contexts. Secondly, based on the feminist analysis it shows that Steven Spielberg's movie wants to illustrate how women escape from oppression are subordinated and exploited in patriarchal society.